The effect of exercise training on intrahepatic triglyceride and hepatic insulin sensitivity: a systematic review and meta-analysis - Sargeant, Jack A.; Gray, Laura J.; Bodicoat, Danielle H.; Willis, Scott A.; Stensel, David J.; Nimmo, Myra A.; Aithal, Guruprasad P.; King, James A. (Wiley, 2018)
This systematic review and meta-analysis determined the impact of structured exercise training, and the influence of associated weight loss, on intrahepatic triglyceride (IHTG) in individuals with non-alcoholic fatty liver disease (NAFLD). It also examined its effect on hepatic insulin sensitivity in individuals with or at increased risk of NAFLD. Analyses were restricted to studies using magnetic resonance spectroscopy or liver biopsy for the measurement of IHTG and isotope-labelled glucose tracer for assessment of hepatic insulin sensitivity. Pooling data from 17 studies (373 exercising participants), exercise training for one to 24 weeks (mode: 12weeks) elicits an absolute reduction in IHTG of 3.31% (95% CI: -4.41 to -2.22%). Exercise reduces IHTG independent of significant weight change (-2.16 [-2.87 to -1.44]%), but benefits are substantially greater when weight loss occurs (-4.87 [-6.64 to -3.11]%). Furthermore, meta-regression identified a positive association between percentage weight loss and absolute reduction in IHTG (β = 0.99 [0.62 to 1.36], P<0.001). Pooling of six studies (94 participants) suggests that exercise training also improves basal hepatic insulin sensitivity (mean change in hepatic insulin sensitivity index: 0.13 [0.05 to 0.21] mg•m-2•min-1 per μU•mL-1), but available evidence is limited and the impact of exercise on insulin-stimulated hepatic insulin sensitivity remains unclear.